Association between hyperglycemia and organ dysfunction in shock patients - Sheila Noberta; Silvia Triratna; Aditiawati Aditiawati; Syarif Husin (Indonesian Pediatric Society, 2013)
Background Hyperglycemia is an important marker of bothpoor clinical outcomes and high mortality rate in critically illpatients. Glucose toxicity results in cell damage that leads toorgan dysfunction.Objective To evaluate for an association between hyperglycemiaand the incidence of organ dysfunction in shock patients.Methods This cross-sectional study was conducted in thepediatric intensive care unit (PICU) of Dr. Moh. HoesinHospital, Palembang from June to November 2011. Subjectswere consecutively-enrolled, shock patients without a historyof diabetes mellitus. Illness severity and organ dysfunction weredetermined by pediatric risk of mortality (PRISM) III score andpediatric logistic organ dysfunction (PELOD) scores, respectively.Hyperglycemia was defined as a blood glucose level 2: 110 mg/dL.Statistical analysis was performed with SPSS version 15.Results Mean age of subjects was 2.30 (SD 2.93) years. MeanPRISM III score was 15 .11 (SD 5 .63). Prevalence of hyperglycemiawas 80.0%. Mean glucose level was 179.51 (SD 86.84) mgldL.Mean PELOD score was 16.02 (SD 13.87). Organ dysfunction wasobserved in 86.7% of subjects. The most common organ dysfunctionobserved in our subjects was liver dysfunction (73.3%). Therewas a significant association between hyperglycemia and organdysfunction (OR43.750;95%CI 4.036 to474.252, P=0.001). Theblood glucose level cutoff points indicative of organ dysfunction,PRISM III score 2: 8, and PELOD score 2: 20.5 were 114.5 mg/dL, 129 mgldL, and 166 mg/dL, respectively.Conclusion There is an association between hyperglycemia andorgan dysfunction. The upper limit blood glucose level indicative oforgan dysfunction is 114.5 mg/dL. A glucose level of 129 mgldL maybe considered to be a warning to start blood glucose monitoring. Alevel above 166 mgldL may be used to indicate the necessity of startinginsulin therapy intervention.